Organic Amendments Alleviate Salinity Effects on Soil Microorganisms and Mineralisation Processes in Aerobic and Anaerobic Paddy Rice Soils - Wichern, Florian; Islam, Md. Rafiqul; Hemkemeyer, Michael; Watson, Conor; Joergensen, Rainer Georg (Frontiers in Sustainable Food Systems, 2020)
Sea-water level rise leads to increased saltwater intrusion causing soil salinity on arable land with negative effects on soil microbial processes. Organic amendments are known to reduce the effects of salinity on soil microorganisms, therefore positively influencing microbial activity and nutrient cycling. However, the extent of this effect in paddy rice soils under aerobic compared to anaerobic conditions is unknown. Consequently, benefits of organic matter addition on carbon (C) and nitrogen (N) mineralisation under saline conditions were evaluated in a short-term laboratory incubation experiment. Two soils from Bangladesh were incubated with rice straw, manure or a manure-rice straw mixture at 50 and 100% water holding capacity (25°C, 27 days). In addition, NaCl was added to half of the samples, which resulted in a set of non-saline (ECe = 1.1-1.3 dS m-1) and saline (ECe = 24.0-32.4 dS m-1) soils. Soil respiration (CO2-release) was measured throughout the experiment. At the end of the experiment, dissolved organic C, inorganic N, microbial biomass as well as bacterial, archaeal and fungal domains were determined. Overall, effects of substrate addition overruled effects caused by salinity and water content. Microbial activity and biomass in particular fungi increased most strongly after rice straw addition and resulted in N immobilisation independent of moisture level. Rice straw and manure alleviated the effects of salinity on microorganisms; these were therefore mainly detectable in the non-amended soils. The reason for this is likely a higher C availability for soil microorganisms after amendment of organic materials, which allows them to produce osmolytes, counteracting the osmotic effects of increased salinity. However, the microbial communities of the two soils under investigation showed different response patterns to salinity reflected by a substantially higher fungi-bacteria ratio in soil B prone to salinity at 50% WHC as compared to soil A. Likewise, the metabolic quotient was higher in soil B and not affected by any of the short term treatments, revealing a soil legacy. Our results highlight the importance of organic amendments, such as rice straw to paddy soils under saline conditions to reduce negative effects on soil microbial processes, allowing them to maintain their major functions.